Firs record of Rhamdella longiuscula from Argentina a new localities for Rhamdella cainguae (Siluriformes: Heptapteridae) - Benitez, Mauricio Fabián (2016)
The genus Rhamdella is considered to becomposed of six species but only R. aymarae andR. cainguae have been recorded from Argentina.Information on the distributions of these species isscarce and R. cainguae is only known from its typelocality. This note documents a wider distribution rangeof R. cainguae and reports R. longiuscula in Argentina forthe first time.